The Female Habitus in the Field Of Bodybuilding and Body Fitness: Gender and Symbolic Domination - Karalius, Mažvydas (Sociologija. Mintis ir veiksmas, 2018)
[full article and abstract in Lithuanian; abstract in English] Based on P. Bourdieu’s concepts of habitus, field and masculine domination, the main objective of this article is to reconstruct the social boundaries of women’s weightlifting and the operating principles of the woman’s habitus within the field of bodybuilding. It is argued that women’s body fitness and women’s bodybuilding are inevitably related to power and gender. An analysis of qualitative, semi-structured interviews with four female athletes (of whom two are female fitness athletes and two others are former female bodybuilders) provides answers to the main research question: what embodied social regulations enable (or restrict) the access of women to an athletic discipline if it is traditionally defined in terms of masculinity? It is further argued that two main criteria arise and take effect in the field of weightlifting: besides the necessity to follow a strict regime and maintain the body in proper shape, a no less important social rule is to embody a socially acceptable form of femininity. The concept of a “synchronized body” is suggested in order to explain the everyday effort to keep the athletic body in between the ever insufficient femininity and the excessive masculinity. Finally, in terms of their bodies, women athletes practice specific strategies in order to suppress the identity conflict between their athletic and “normal,” mundane lives.